Relações verticais colaborativas e mensuração contábil : uma análise da abordagem ABC - Dias, Wellington Amaral (2005)
In face of a growing competitive atmosphere, the firms have been guiding for a model of set administration collaborative relationships, which settle down the need of managerial information that reach beyond the organizational limits supporting the managers in the coordination of activities of a firma that affect the acting of another. The collaborative ambient brings new challenges for the administration of these relationships, making to raise problems of appropriation interests on the generated benefits the affect the level of trust of relationship. The availability of accounting information acts in this context as a control element that correlates the availability of accounting information with the request trust. Several researched authors criticize the inadequacy of the accounting information in this environment what became then the objective of the research in the search of answers to this questioning. This dissertation presents a case study of an application of costs in ABC approach, in an atmosphere of relationships interfirms in collaboration. The objective of this study is to investigate the role of the managerial informations supported by the ABC costs approach through a study of case of an application of this approach of costs to support the decision-making of prices formation. This decision-making of inserted in a context of a collaborative relationships between Peixoto Wholesaler and customers retailer segment of the supermarkets, managed for the unit de business denominated Rede Valor. The role of the accounting information is interpreted being observed the purpose of the collaborative relationships in the value chain, where there is predominance of logistical activities, purchases and marketing in a way to give context to the decisive model of these relationships. The social atmosphere of these relationships is investigated being interpreted managerial information availability. Soon after is investigated the ABC cost approach that in the revision of literature is pointed as potential supplier of costs information, exploring the state of the art of this approach through theoretical models of implementation in this environment. The research concluded that there is a lack of accounting informations suitable to the interfirms atmosphere to support decisions observing all the value chain. The ABC tool shows itself useful to support decisions in this environment, but its complex implementation turns it difficult to be up-to-date in a context of operational changes, with questionings about its costs and benefits, as related in the bibliographical revision. Additionally, the study confirms empirically the relevance of the trust level among the firms as an influenced element on the accounting information availability in this environment.